PENERAPAN PENDEKATAN SUPERVISI KOLABORATIF UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU MADRASAH - Syarifudin (Jurnal Literasi Pendidikan Dasar, 2023)
This school action research aimed to improve the ability and performance of school principals in applying a collaborative supervision approach to increase the professional competence of teachers at MIN/MIS Kabupaten Manggarai Barat. The study found that the collaborative supervision approach involved three stages: collaborative pre-supervision, collaborative supervision, and post-collaborative supervision. The research progressed from cycle 1 to cycle 2, and there was an improvement in the professional competence of teachers. In the pre-cycle stage, the average professional competence score of teachers was 52.27 with less criteria. In cycle 1, the score increased to 70.45 with sufficient criteria, which is an improvement of 18.18 points. Additionally, there was a further increase in professional competence from cycle 1 to cycle 2, with an improvement of 18.19 points. The average teacher professional competence in cycle 2 was 88.64 with good criteria. The results of this study highlight the effectiveness of the collaborative supervision approach in enhancing teacher professional competence, which can positively impact the quality of education in schools.